Patagonia's path to carbon neutrality by 2025 - Kammen, Daniel M., 1962- (SAGE Knowledge. Cases., 2018)
This case study describes Patagonia's goal to become carbon neutral by 2025 in an absolute sense--that is to reduce emissions to zero while still growing the company. Patagonia also wants to achieve absolute carbon neutrality in such a way that other interested companies can replicate. The case explores aspects of this goal through the eyes of a number of Patagonia employees who work on different teams within the apparel and gear business. (As a whole, Patagonia includes both the long-established apparel and gear operations and the more-recently formed food line Provisions. However, the company's goal, as described in the case, excludes Provisions-related emissions).